Perancangan Desain Digital Fotografi Produk Sebagai Media Promosi Pada UMKM Peyek Kriuk Mak Koles Untuk Meningkatkan Daya Tarik Konsumen - Adit, Ambar Aditya Putra; Rika, Rika Febri Sasmita; Dika, Dika Tondo Widakdo; Inggrit, Inggrit Prila Septiana (GESTALT : JURNAL DESAIN KOMUNIKASI VISUAL, 2025)
In today's rapidly evolving modern era, product marketing through digital media has become a highly important aspect, especially for micro, small, and medium enterprises (MSMEs). Technological advancements have given rise to various online platforms that enable products to be presented in an attractive and professional manner. One effective strategy to enhance product appeal is through the use of high-quality product photography. Aesthetic and engaging visuals can capture the attention of potential consumers, build trust, and strengthen brand image. For MSMEs like Peyek Kriuk Mak Koles, product visualization becomes a strategic step in expanding market reach. By utilizing modern photography technology, products can be showcased with detail and a strong professional impression. This not only increases buying interest, but also serves as a tool to reinforce branding and competitiveness in the highly competitive digital marketplace. A product photoshoot session serves as a crucial moment to optimize promotion efforts and support business growth, all while integrating elements of digital design for maximum visual impact.